The Role of Ecosystems in Determining Climate: The Special Case of The Amazon Rainforests (2008)
Titulo en español:  La Importancia de los Ecosistemas en la Determinación del Clima: Caso Especial los Bosques de la AmazoniaRESUME:The summer floods in England, following deluges of rain more resonant of the Amazon, the searing, deadly heat in Southern Europe, with temperatures at times exceeding 45°C, should be enough to silence those who stalwartly maintain that we are experiencing no more than natural swings in climate. Those scep- tics, who have insisted that long term changes in the Earth’s orbit as well as in the flux of sunlight are accountable for the extreme weather and global warm- ing, have basically been routed.